Short communication. A new host and phenotypic variation of Phytophthora hedraiandra in Spain - Moralejo, E.; Belbahri, L.; Clemente, A.; Lefort, F.; Descals, E. (Spanish Journal of Agricultural Research, 2007)
The oomycete Phytophthora hedraiandra De Cock & Man in’t Veld is first reported in Spain on the ornamental plant Rhododendron catawbiense Michx., as well as on leaves of Viburnum tinus L. in nurseries. The identification of these isolates was carried out by examining their morphological and cultural features, and by comparing the sequence of the nuclear rDNA ITS region and the mitochondrial cox1 gene with those published in GenBank database. The phenotypes of the isolates fitted the species description, but a higher intraspecific variation was noticed in respect to their sporangial size, colony pattern and radial growth rates. Due to the similarities between P. cactorum (Lebert et Cohn) and P. hedraiandra, the taxonomy and host ranges of the P. cactorum/P. hedraiandra complex in ornamental nurseries and natural ecosystems need reviewing.